Vegetation Analysis and Propagation of Ground Cover Plants in Soil Affected by Sidoarjo Mud - Saiful Arifin; Listriani Listriani (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study was to determine the structure of vegetation and the predom- inance of types and propagation of ground cover plants on land affected by the Sidoarjo mudflow. The study was conducted in the villages of Gempolsari, Sentul and Kuaron from April-May 2015. The research was descriptive through analysis of vegetation using the line inception method to obtain the Important Value Index (INP) and observing the vegetative vegetative method of dominant land cover. The results of the study showed that the vegetation structure of 11 types of soil cover plants in mud-affected land was dominated by Panicum sp, Panicum maximum, and Arthraxon sp with INP 29.60, 17.70, and 16.84 followed by plant species with INP below successively: Cynodon dactylon (Linn .) Prest, Spigelia anthelmia L, Mimosa pudica, Cyperus Rotundus, Imperata Cylin- drica, D. aegyptium (Linn.) P. Beauv. Desmidium sp, and A. villosa Willd. The three types of soil cover plants are predominantly vegetative by rhizome (roots) and saplings, while generatively using seeds.